Deep accidental hypothermia accompanied with cardiac arrest after alcohol and drug poisoning treated with extracorporeal life support. (2018) - Grapatsas, Konstantinos; Leivaditis, Vasileios; Panagiotopoulos, Ioannis; Spiliotopoulos, Konstantinos; Koletsis, Efstratios; Dahm, Manfred; Kosmidis, Christoforos; Laskou, Stella; Zarogoulidis, Paul; Katsaounis, Athanasios; Pavlidis, Efstathios; Giannakidis, Dimitrios; et al.
Abstract: Deep accidental hypothermia is an unusual clinical entity in developed countries. We report a case of a 30 year old male Caucasian patient with accidental severe hypothermia who was transferred to the emergency department of our hospital after prolonged exposure in the urban city's night environment cold as a result of alcohol and drugs abuse. The patient was found unconscious in the first early hours from onlookers. The time that the patient remained unconscious is unknown. During the transfer to the hospital because of cardiac arrest cardiopulmonary resuscitation began. In the emergency department an extracorporeal life support system (ECLS) was implanted under cardiopulmonary resuscitation in order to achieve hemodynamic stabilization and rapid and safe rewarming. The patient's rewarming lasted 6 hours. The patient was extubated the next day.